Broad‐Spectrum Antimicrobial and Biofilm‐Disrupting Hydrogels: Stereocomplex‐Driven Supramolecular Assemblies1. Issue 2 (19th November 2012) - Li, Yan; Fukushima, Kazuki; Coady, Daniel J.; Engler, Amanda C.; Liu, Shaoqiong; Huang, Yuan; Cho, John S.; Guo, Yi; Miller, Lloyd S.; Tan, Jeremy P. K.; Ee, Pui Lai Rachel; Fan, Weimin; et al.
<x xml:space="preserve">Abstract</x> Fighting the resistance: Biodegradable and injectable/moldable hydrogels with hierarchical nanostructures (see picture) were made with broad‐spectrum antimicrobial activities and biofilm‐disruption capability. They demonstrate no cytotoxicity in vitro, and show excellent skin biocompatibility in animals. These hydrogels have great potential for clinical use in prevention and treatment of various multidrug‐resistant infections.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>